2015
DOI: 10.1186/s12958-015-0047-7
|View full text |Cite|
|
Sign up to set email alerts
|

Uterine NDRG2 expression is increased at implantation sites during early pregnancy in mice, and its down-regulation inhibits decidualization of mouse endometrial stromal cells

Abstract: BackgroundN-myc down-regulated gene 2 (NDRG2) is a tumor suppressor involved in cell proliferation and differentiation. The aim of this study was to determine the uterine expression pattern of this gene during early pregnancy in mice.MethodsUterine NDRG2 mRNA and protein expression levels were determined by RT-PCR and Western blot analyses, respectively, during the peri-implantation period in mice. Immunohistochemical (IHC) analysis was performed to examine the spatial localization of NDRG2 expression in mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…We followed a previously described method of collecting uterine tissue at different stages of pregnancy (Gu et al, ). Uterine tissue was collected from pregnant mice on Days 0.5, 3.5, 4.5, 5.5, and 8.5 of pregnancy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed a previously described method of collecting uterine tissue at different stages of pregnancy (Gu et al, ). Uterine tissue was collected from pregnant mice on Days 0.5, 3.5, 4.5, 5.5, and 8.5 of pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…The isolation and culture of mouse ESCs was performed as described previously (Gu et al, ). On the 4th day of pregnancy, uterine horns were collected, trimmed, cleaned, and slit longitudinally.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described (Gu et al, ). Briefly, the collected mouse uterine tissues were fixed in 4% paraformaldehyde in phosphate‐buffered saline (PBS) and then embedded in paraffin (Leica, Wetzlar, Hessen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Given that NDRG1 plays important roles in cell proliferation and differentiation and that another three members of the NDRG family, NDRG2 (Gu et al, ), NDRG3 (Yang et al, ) and NDRG4 (Yang, Gu et al, ), have been recently identified to be involved in the decidualization of mouse endometrial stromal cells (ESCs), we hypothesized that NDRG1 might participate in the regulation of the implantation process, especially in the differentiation of ESCs. Thus, the current study was carried out to examine the uterine expression pattern of NDRG1 during the peri‐implantation period in mice, to observe the association of the NDRG1 expression level with pregnancy loss in mice and to observe the in vitro differentiation of human and mouse ESCs.…”
Section: Introductionmentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors noticed an error in Fig. 5 : in panel c, the bands produced by NDRG2 and beta-actin were incorrectly labelled.…”
mentioning
confidence: 99%